Chữ Việt trong xử lí truyền thông - Việt, Ngô Trung (Journal of Computer Science and Cybernetics, 2016)
In this paper, the relation between representing of Vietnamese characters, computer processing and communication, concerning with the Vietnamese standard code, will be discussed. Two architectures for representing Vietnamese characters: Precomposed and separated are presented. Based on that, some arguments about setting up a Vietnamese standard code for processing and communication are discussed. This standard code proposal consists of three separated code tables but unified in the same framework and satisfied all requirements about Vietnamese characters in computer processing and communication.